LAW ENFORCEMENT OF HATE SPEECH CRIMINALS THROUGH SOCIAL MEDIA BASED ON INDONESIA’S POSITIVE LAW - Stephanus Pelor (International Journal of Multidisciplinary Research and Literature, 2023)
Technological developments have provided convenience for people in various aspects of life. To prevent and deal with the negative impacts of technological developments, effective and efficient efforts are needed. This includes implementing appropriate laws and regulations to protect society from technological crime. Government and non-government organizations, as well as technology companies, also need to work together to strengthen cyber security, increase public awareness of the risks of digital crime, and educate users about safe practices in using technology. The normative juridical research method that you mentioned is the right approach to study laws and legal theories related to criminal acts, especially hate speech through social media, based on Indonesian positive law. The statutory approach in normative juridical research focuses on an analysis of existing laws and regulations. Referring to the Chief of Police Circular Letter Number SE/06/X/2015 concerning Handling Hate Speech, the police pay attention to and implement preventive measures in dealing with hate speech. The circular letter provides guidance for law enforcement officials in handling hate speech cases. The handling of hate speech in Indonesia is helped by the existence of the ITE Law which contains more detailed rules regarding crimes committed through electronic media, but also presents several obstacles, firstly the police factor, where complaints are still being made. Many perpetrators do not understand that their actions are defamation. They think what they are doing is just a demonstration of bullying or dissatisfaction with a party. Even if the act harms another person, it can be prosecuted